A Charge‐Switchable Zwitterionic Peptide for Rapid Detection of SARS‐CoV‐2 Main Protease. Issue 9 (14th January 2022) - Jin, Zhicheng; Mantri, Yash; Retout, Maurice; Cheng, Yong; Zhou, Jiajing; Jorns, Alec; Fajtova, Pavla; Yim, Wonjun; Moore, Colman; Xu, Ming; Creyer, Matthew N.; Borum, Raina M.; et al.
Abstract: The transmission of SARS‐CoV‐2 coronavirus has led to the COVID‐19 pandemic. Nucleic acid testing while specific has limitations for mass surveillance. One alternative is the main protease (M pro ) due to its functional importance in mediating the viral life cycle. Here, we describe a combination of modular substrate and gold colloids to detect M pro via visual readout. The strategy involves zwitterionic peptide that carries opposite charges at the C‐/N‐terminus to exploit the specific recognition by M pro . Autolytic cleavage releases a positively charged moiety that assembles the nanoparticles with rapid color changes ( t <10 min). We determine a limit of detection for M pro in breath condensate matrices <10 nM. We further assayed ten COVID‐negative subjects and found no false‐positive result. In the light of simplicity, our test for viral protease is not limited to an equipped laboratory, but also is amenable to integrating as portable point‐of‐care devices including those on face‐coverings. Abstract : A rapid colorimetric detection of SARS‐CoV‐2 protease using a zwitterionic peptide and gold colloids is reported. The sensor showed good performance in exhaled breath condensate with a limit of detection in the low nanomolar range. This technology can be integrated into regular face coverings for COVID‐detection.